A high-throughput drug discovery pipeline to optimize kidney normothermic machine perfusion - Hofmann, Smilla; Grahammer, Florian; Edenhofer, Ilka; Puelles, Victor G.; Huber, Tobias B.; Czogalla, Jan (Frontiers in Physiology, 2022)
Kidney transplantation is the only definitive therapy for end-stage kidney disease. The shortage of organs for transplantation is the main limitation of this life-saving treatment. Normothermic machine perfusion (NMP) is a novel preservation technique with the potential to increase the number of transplantable kidneys through reducing delayed graft function and organ evaluation under physiological conditions. To date, the cellular effects and possible pharmacological interventions during machine perfusion are incompletely understood. A major limitation is the technically complex, time-consuming, and small-scale replication of NMP in rodent models. To overcome this, we developed a 3D-printed, high throughput ex-vivo mouse kidney slice incubator (KSI) mimicking mouse kidney NMP by working under closely resembling conditions. KSI significantly reduced the time per experiment and increased the sample throughput (theoretical: 54 incubations with n = 500/day). The model recapitulated the cellular responses during NMP, namely increased endoplasmic reticulum stress (ER stress). Using KSI, five pharmacological interventions against ER stress taken from the literature were tested. While four were ineffective and excluded, one, β-Nicotinamide-adenine-dinucleotide (NADH), ameliorated ER stress significantly during KSI. The test of NADH in mouse kidney NMP replicated the positive effects against ER stress. This suggests that testing the addition of NADH during clinical kidney NMP might be warranted.